Penggunaan Al-Qur’an Kisah The Fantastic Adventure Dalam Meningkatkan Motivasi Belajar Al-Qur’an Santri Pondok Pesantren Rahmatul Asri - Nurvadillah Nurvadillah; Muhammad Saleh; Muh. Dahlan; Usman Usman; Marhani Marhani; Khaerul Muawan (Journal on Education, 2024)
This thesis discusses the use of Al-Qur'an The Fantastic Adventure in enhancing the learning motivation of Al-Qur'an among students at Rahmatul Asri Islamic Boarding School. This research aims to understand the concept of the storytelling approach in Rahmatul Asri Islamic Boarding School and examine the influence of using Al-Qur'an The Fantastic Adventure on students' learning motivation at Rahmatul Asri Islamic Boarding School. The study employed a pre-experimental method with a one-group pretest-posttest design, involving 34 female students from Grade VII of MTs Rahmatul Asri. Data were collected through a concept comprehension test and a learning motivation questionnaire administered before and after the treatment. The findings of the study showed a significant improvement in students' concept comprehension and learning motivation. The average Primary Motivation of the students increased from the "fair" category (55.89%) to the "very high" category (80.51%) after the treatment. The Secondary Motivation also increased from the "fair" category (53.57%) to the "very high" category (84.89%). Data analysis using the t-test indicated that this improvement was significant, with a sig value (2-tailed) of 0.000 < 0.05, indicating that the difference did not occur by chance. The conclusion of this study is that using Al-Qur'an Kisah The Fantastic Adventure is effective in enhancing students' learning motivation. Interactive and engaging learning media can create a more active and enjoyable learning environment. It is recommended that this method be widely implemented in other pesantren, and teachers be trained to optimize the use of interactive media in teaching.